Self-DNA Sensing by cGAS-STING and TLR9 in Autoimmunity: Is the Cytoskeleton in Control? - Amadio, Roberto; Piperno, Giulia Maria; Benvenuti, Federica (Frontiers in Immunology, 2021)
Modified or misplaced DNA can be recognized as a danger signal by mammalian cells. Activation of cellular responses to DNA has evolved as a defense mechanism to microbial infections, cellular stress, and tissue damage, yet failure to control this mechanism can lead to autoimmune diseases. Several monogenic and multifactorial autoimmune diseases have been associated with type-I interferons and interferon-stimulated genes (ISGs) induced by deregulated recognition of self-DNA. Hence, understanding how cellular mechanism controls the pathogenic responses to self-nucleic acid has important clinical implications. Fine-tuned membrane trafficking and cellular compartmentalization are two major factors that balance activation of DNA sensors and availability of self-DNA ligands. Intracellular transport and organelle architecture are in turn regulated by cytoskeletal dynamics, yet the precise impact of actin remodeling on DNA sensing remains elusive. This review proposes a critical analysis of the established and hypothetical connections between self-DNA recognition and actin dynamics. As a paradigm of this concept, we discuss recent evidence of deregulated self-DNA sensing in the prototypical actin-related primary immune deficiency (Wiskott-Aldrich syndrome). We anticipate a broader impact of actin-dependent processes on tolerance to self-DNA in autoimmune disorders.